Kosovo : Poverty assessment, Volume 1. Accelerating Inclusive Growth to Reduce Widespread Poverty - World Bank (Washington, DC, 2012)
Poverty in Kosovo is widespread and has remained persistent in the first half of this decade. The evidence suggests that poverty is higher among those who live in families that are large, have many unemployed members, and have low education levels. The poor are also geographically concentrated in rural areas and a few regions. The main message of this report is that the slow and volatile growth was doubly disadvantageous. The first disadvantage was that it did not enable a significant fraction of the population to earn their way out of poverty. The second disadvantage was that by constraining the government's revenue base, it made it difficult for many families to receive adequate public protection against shocks. Therefore, to improve welfare in the future, the report recommends a focus on generating high and sustainable growth by improving urban services and infrastructure and addressing inequities in the access to secondary and higher education for the poorest population transitioning out of over-reliance on migration, and improving the targeting and expansion of the social assistance program if the revenue base of the government improves over time.